Identifying the Essential Components of Strength-based Technology Clubs for Adolescents with Autism Spectrum Disorder. (4th July 2021) - Jones, Matthew; Falkmer, Marita; Milbourn, Ben; Tan, Tele; Bölte, Sven; Girdler, Sonya
ABSTRACT: Background : Strength-based technology clubs for adolescents with autism spectrum disorder (ASD) have become increasingly popular; however, they remain poorly described in the literature. Before the impact and benefit of strength-based technology clubs can be measured, consistency in their design and delivery must be established. This study aimed to identify the essential components of strength-based technology clubs by exploring context, mechanisms, and outcomes of existing strength-based technology clubs. Method : Twenty-three adolescents with ASD (mean age 12.96 years, SD = 1.86, range = 10–18 years), 25 parents (mean age 46.08 years, SD = 8.27, range = 33–69 years), and 20 facilitators (mean age 27.93 years, SD = 6.55, range = 20–46 years) were purposively sampled from three established strength-based technology clubs. Data were obtained via ethnographic methods, including participant observations, interviews, and focus groups. Data analysis was underpinned by a realist evaluation, which provided the context-mechanism-outcome framework. Results : Data analysis revealed that strength-based technology clubs had four context themes (personal factors of adolescents, personal factors of facilitators, personal factors of parents, institution), three mechanism themes (activity design, strengths and abilities, environment), and three outcome themes (skill building, connection with others, emotion). Conclusion : The results highlighted the importance of understanding the personal context of adolescents, providing an individualized approach, leveraging individual interests, and modifying the environment to suit the individual. The findings contributed to defining a strength-based approach within ASD, and have demonstrated that positive outcomes can be achieved by focusing on strengths rather than deficits. Future ASD services can use the results as a framework for applying a strength-based approach. The efficacy of newly designed strength-based programs can then be tested.